The role of capability and ambidexterity in enhancing the startup performance - Mawaddah Akmalia; Rifelly Dewi Astuti (President University, 2022)
Digitization offers great opportunities for the business environment, including startup companies. Responding to the pressure of technology, many startup companies are using digital platforms as their business strategy. However, many startups fail due to the absence of a comparable digital platform capability. In addition, startups face unique challenges because of their limited resources, so startups must be able to manage their network capability and ambidexterity which consists of exploitation orientation and exploration orientation. With this capability and orientation, it is hoped that startup companies can improve their startup performance. This study aims to empirically examine the influence of digital platform capability, both directly and influenced by network capability, on startup performance and also to determine the moderating effect of ambidexterity which is divided into exploitation orientation and exploration orientation between network capability and startup performance. The survey was conducted on 124 digital-based startups in the service sector in Indonesia. Furthermore, the survey results were analyzed using the structural equation modeling-partial least square (SEM-PLS) to test the hypothesis. The result is that digital platform capability and network capability affect startup performance. Meanwhile, the moderation of exploitation orientation and exploration orientation towards the relationship between network capability and startup performance produces different results.